REPRESENTASI IDEOLOGI DAN KEKUASAAN DALAM BAHASA: KAJIAN TEKS MEDIA - Suharyo, Suharyo; Surono, Surono; Amin, Mujid F (HUMANIKA, 2015)
This article is based on the assumption that language is not in a social vacuum. Language is more than a set of words that merely linguistic, but also social. Therefore, the current linguistic research should take into account the social dimension in the analysis are critical, such as van Dijkâ€™s critical discourse analysis (CDA) research model. The critical discourse analysis researchÂ  considering the text, context, social cognition, and analysis/social context. Research steps include: exposing the macro structure (thematic), superstructure (schematic), and microstructure consisting of semantics, syntax, stylistic, and rhetoric. Accordingly, this study uses the method read and record while research data has been collected from Suara Merdeka and Kompas newspaper. Finally concluded that the language represents the ideology and power (symbolic) both individual and communal.